The impact of globalization on the innovative activity of the state - Shabalina L. V., Timko M. V., Rubtsova V. A. (Relevant issues of management, economics and economic security, 2022)
The article identifies the main forms of globalization in the innovation sphere, analyzes the main trends in the innovative development of the countries of the world. It is determined that the conditions of globalization will benefit the states that are able to ensure a leading role in their economy of high-tech industries and knowledge-intensive services in combination with the strengthening of the spheres of science and education.
Keywords: инновации; глобализация; патентные заявки; инновационная деятельность государства; Глобальный индекс инноваций